The Impact of Government Size on Corruption: A Meta-Regression Analysis - Graziella Bonanno; Lucia Errico; Nadia Fiorino; Roberto Ricciuti (Center for Economic Studies and ifo Institute (CESifo), 2024)
We perform a Meta-Regression Analysis (MRA) of the literature on government size and corruption, examining 450 empirical estimates retrieved from 44 primary papers published from 1998 to 2022. We find considerable heterogeneity in the results, mainly depending on whether the paper is published or not, accounts for endogeneity and uses panel or cross-sectional data. Moreover, the type of indicator used to measure corruption has a significant impact on the sign of the relationship with government size. Finally, adding variables defined at the country level as regressors, per capita GDP does not lead to significant results, whereas we find a positive relationship between the countries' corruption index and the effect size.
Keywords: H11; H50; D73; C83; 330; corruption; survey; government size; public expenditure; meta-analysis